Giant cell tumour of the femur in a 9-year-old girl, resulting in severe leg length discrepancy. (21st March 2016) - Oba, Masatoshi; Inaba, Yutaka; Machida, Jiro; Saito, Tomoyuki
Abstract : Giant cell tumour of bone (GCTB) is a rare benign tumour noted before physeal closure. GCTB cases in patients younger than 10 years are especially uncommon. The authors report the case of a 9-year-old girl with a GCTB of the distal femur. After initial intralesional excision and curettage of the tumour, local recurrence occurred, which needed two more additional surgeries to treat. The primary tumour and the local relapse invaded the growth plate of the right distal femur, leading to growth disturbance of the femur and requiring leg lengthening using Ilizarov apparatus. Surgeons should note the possibility of this rare condition while treating radiographic lytic lesions even in skeletally immature patients. The occurrence of late limb length discrepancy would be more likely in younger patients.